2014
DOI: 10.1017/s1460396914000053
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the feasibility of using CT (±diagnostic MRI) instead of MRI at brachytherapy in image guided brachytherapy in cervical cancer

Abstract: Purpose: To compare the contours and dose volume histograms (DVH) parameters of the high-risk clinical target volume (HRCTV) contoured on computed tomography (CT) using clinical findings at brachytherapy, clinical findings at brachytherapy with magnetic resonance imaging (MRI) at diagnosis and HRCTV defined on MRI at brachytherapy in cervical cancer patients. Materials and methods:Fifteen patients undergoing MRI-guided image-based brachytherapy underwent both CT and MRI after applicator insertion. Two sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Bhavana et al . showed similar findings, with the mean difference in dose per fraction less than 1 Gy [ 8 ].…”
Section: Purposementioning
confidence: 53%
See 1 more Smart Citation
“…Bhavana et al . showed similar findings, with the mean difference in dose per fraction less than 1 Gy [ 8 ].…”
Section: Purposementioning
confidence: 53%
“…Past studies have shown that CT-delineated HRCTV (HRCTV ct ) is statistically different from MRI-delineated HRCTV (HRCTV mri ) , even with pre-planning MRI [ 3 , 6 , 7 , 8 , 9 , 10 ]. Such volumetric difference has translated into change in HRCTV D 90 , while dose to OAR show no statistical difference.…”
Section: Purposementioning
confidence: 99%
“…Viswanathan et al proved that the HRCTVct D90 in CT-based plans is statistically lower than the HRCTVmri D90 in MRI guided plans, with mean doses per fraction of 6.7 Gy vs. 8.7 Gy, respectively [ 25 ]. Bhavana et al showed similar findings, with the mean difference in dose per fraction less than 1 Gy [ 26 ].…”
Section: Image Guidance Target Definition and Treatment Adaptatiomentioning
confidence: 65%
“…Past studies have shown that high-risk clinical target volumes (HRCTVs) in cervix tumors delineated by CT (HRCTVct) are statistically different from MRI-delineated HRCTVs (HRCTVmri), even with pre-planning MRI [ 24 , 26 , 27 , 28 , 29 ]. Such volumetric differences have translated into change in HRCTV D90, while the dose to OAR shows no statistical difference.…”
Section: Image Guidance Target Definition and Treatment Adaptatiomentioning
confidence: 99%
“…Rai et al . [ 22 ] reported that the height was significantly underestimated in CTV HR -CT contours; however, the statistics were similar between the heights of CT + MRI at diagnosis (CTV HR -CT dMRI ) and CT + MRI at BT (CTV HR -MR). Viswanathan et al .…”
Section: Discussionmentioning
confidence: 93%